(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
The stratigraphy and paleogeography of the ladinian Esino Limestone outcropping in Valle Brembana-Valle Parina, have been integrated with the biostratigraphic analysis of cephalopod fauna. A complex internal structure of the upper anisian-ladinian Esino carbonate platform has been identified. Six different lithozones have been recognized, they record the stratigraphic-paleogeographic evolution of the Esino Limestone. This carbonate platform developed through three stages: 1) construction of a lower edifice (Late Anisian-? Early Ladinian) representing the first phase of carbonate piatform diffusion on structural highs, which were already the site of carbonate deposition during the Middle Anisian (peritidal dolomites of the Angolo Limestone); 2) buildup of the carbonate complex (main edifice). In this second phase (Early Ladinian-Late Ladinian p.p.) the most important one, the platform growth took place by prevalent aggradation; 3) development of the upper edifice and progradation of the piatform in the Late Ladinian. In this third phase, inner plarform facies with diagenetic caps at the top of peritidal cycles are common. The buildup developed in the second phase yields bioclastic packstones with ammonoids, gastropods, echinoderms, and bivalves clustered within lithozone 4 and in the proximity of the southern margin of the platform in Val Parina. Studies in progress of ammonoids and gastropods allowed for the recognition of different fossil assemblages which date from Early Ladinian to Late Ladinian. A few problematic ammonoid assemblage of probably Early Ladinian age, has been found in a stratigraphic level above the base of the Esino Limestone.